2021
DOI: 10.1029/2020wr029094
|View full text |Cite
|
Sign up to set email alerts
|

Catchment Functioning Under Prolonged Drought Stress: Tracer‐Aided Ecohydrological Modeling in an Intensively Managed Agricultural Catchment

Abstract: In line with long-term climate change projections, the extreme drought in 2018-2019 provided a unique opportunity to investigate expected regional climate change impacts both in terms of monitoring (e.g., the TERENO observatories in Germany [Heinrich et al., 2019; Wollschläger et al., 2016]) and modeling (e.g., Samaniego et al., 2018; Smith et al., 2020a) flux-storage dynamics. As drought impacts propagate through a catchment's ecohydrological cycle (Wilhite & Glantz, 1985), increasingly dry conditions (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…Third, including a moderate drought (the 2017 event) in the calibration did not lead to an improvement in Q and ET simulation during a severe drought (the 2022 event), with mean KGE = 0.18 for Q across the study sub-catchments, and mean r = -0.11 and nRMSE = 1.85 for ET across the croplands during 2022. Yang et al (2021) reported that an ecohydrological model better simulated Q in an experimental German catchment during the 2018-2019 drought when including it in the calibration period. However, here we proved that calibrating during a moderate drought was not sufficient to improve model transferability to a different and more severe drought.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, including a moderate drought (the 2017 event) in the calibration did not lead to an improvement in Q and ET simulation during a severe drought (the 2022 event), with mean KGE = 0.18 for Q across the study sub-catchments, and mean r = -0.11 and nRMSE = 1.85 for ET across the croplands during 2022. Yang et al (2021) reported that an ecohydrological model better simulated Q in an experimental German catchment during the 2018-2019 drought when including it in the calibration period. However, here we proved that calibrating during a moderate drought was not sufficient to improve model transferability to a different and more severe drought.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…Multivariable calibration may be helpful to improve model internal consistency (Dembélé et al, 2020;Duethmann et al, 2022), also during low-flow periods (Rakovec et al, 2016a) and droughts (Yang et al, 2021). Yang et al (2021) for example showed that including tracer data in the calibration of an ecohydrological model increased model internal consistency during the 2018-2019 drought in Central Europe. Here we calibrated the model against Q data only (Section 2.4.2).…”
Section: Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying catchment-scale water cycling over longer periods is important as wet and dry precipitation cycles can adversely affect blue (groundwater and discharge) and green (evapotranspiration) water fluxes and storage dynamics (Orth & Destouni, 2018;Yang, Tetzlaff, Soulsby, Smith, & Borchardt, 2021). Spatially distributed modelling approaches are, in many circumstances, essential for spatio-temporal evaluation of the non-stationarity of flow paths and storages within catchments (Fatichi et al, 2016).…”
Section: Descriptionmentioning
confidence: 99%